Effect of combined application of high- and low-intensity lasers on dentin hypersensitivity: A randomized clinical trial - Zohreh Tabibzadeh; Reza Fekrazad; Azadeh Esmaeelnejad; Mohammad Mostafa Shadkar; Zahra Khalili Sadrabad; Morteza Ghojazadeh (Tabriz University of Medical Sciences, 2018)
Background. Diode lasers (DLs) have demonstrated equal or better desensitizing effects than fluoride varnish, 10% potassium nitrate (NK) gel and Gluma. The current study evaluated the desensitizing effect of combined application of DLs with two different output powers and compared it with single DL therapy. Methods. Sixty-two hypersensitive teeth were allocated randomly into two groups: the single group was treated with 3-W DL beam once and in the combined group, the teeth were irradiated three times (the first time with 0.2-W and then with 3-W and the second and third times, 48 and 96 hours after the baseline visit, with 0.2-W DL beams). The amount of dentin hypersensitivity (DH) was evaluated, immediately before and after each visit, and 1 week and 1 and 3 months after the first visit. Data analysis was performed using chi-squared test, repeated measurement of ANOVA and Mann-Whitney U test. P<0.05 was considered statistically significant. Results. Statistically significant changes were observed in the means of VAS indices between all the measurement intervals and pretreatment measures, in both experimental groups (P<0.001). The difference in VAS reduction among the groups was not significant when the hypersensitive teeth were stimulated by a periodontal probe and a jet of air (P=0.63 and P=0.12). Conclusion. The results of the present study showed that using both high-intensity and combined DL beams gives rise to significant reductions in DH. There was no significant difference between combined and single laser therapies in the treatment of tooth hypersensitivity.